IMPLEMENTASI PEMBELAJARAN MEMBACA AL-QUR’AN MELALUI METODE THORIQOTY DI SEKOLAH MI AL-FATIMAH KOTA BOJONEGORO - Sholiya Wilda Shobirina; Muhammad Sulistiono; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Education is very important in the era of globalization. Where, in fact education is an effort that has been made to raise a point of view. Therefore, each education that will be given by teachers to students in elementary schools is one of the religious educations that parents pay less attention to. is education to read the Qur'an. In general, parents only focus on students regarding general education and it is quite limited for parents to pay attention to one of the religious educations, namely learning to read the Qur'an. However, it will be seen in the development of students, especially at the elementary level, which is quite limited in reading the Qur'an which is equivalent to the instructions and knowledge of tajwid is quite correct. Therefore, in the current era of globalization, learning the Qur'an will be needed in the world of education, both formal and non-formal schools for elementary school students. Thus, Al-Fatimah Elementary School agreed that learning to read the Qur'an through the Thoriqoty method would be carried out every morning. However, the existence of these activities at the Al-Fatimah school hopes that one day students will be able to read the Qur'an quite well and correctly. Keywords: Implementation, Reading the Al-Qur’an, Thoriqoty Method.